2009
DOI: 10.1007/s10689-009-9285-1
|View full text |Cite
|
Sign up to set email alerts
|

Germline MLH1 and MSH2 mutations in Italian pancreatic cancer patients with suspected Lynch syndrome

Abstract: Lynch syndrome is an inherited cancer syndrome caused by germline mutations in mismatch repair (MMR) genes MLH1, MSH2, MSH6 and PMS2. LS predisposes to high risk of early-onset colorectal, endometrial and other tumors. Patients with Lynch syndrome have also been shown to have an elevated risk for pancreatic cancer (PC). In this study, we aimed to estimate the frequency of suspected Lynch syndrome among a series of 135 PC patients. Further, we wanted to determine the frequency of MMR gene mutations in the suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…They also found that it did not segregate with disease in two families, and noted that these observations together are consistent with a low-penetrance Lynch syndrome mutation. Gargiulo et al 56 came to the same conclusion after finding K618A in an unaffected branch of a Lynch syndrome family. Our observations confirm these findings and also greatly extend them.…”
Section: In Silico Analysismentioning
confidence: 71%
“…They also found that it did not segregate with disease in two families, and noted that these observations together are consistent with a low-penetrance Lynch syndrome mutation. Gargiulo et al 56 came to the same conclusion after finding K618A in an unaffected branch of a Lynch syndrome family. Our observations confirm these findings and also greatly extend them.…”
Section: In Silico Analysismentioning
confidence: 71%
“…Pedigree review was conducted for 225 PC patients enrolled between February 1999 and February 2011 within the framework of an ongoing case-control study on the genetics of PC [21][22][23]. The study was approved by the Ethics Committees of the three participating hospitals (San Martino Hospital, Galliera Hospital and National Cancer Institute).…”
Section: Study Populationmentioning
confidence: 99%
“…Finally, Panel C shows simple familial aggregation, with several malignancies in the family, but no apparent verticality for pancreatic cancer (see Figures 2, 3). The most frequently reported cancers in the relatives of probands were those of the breast (43 cases, 16.5% of the total), central nervous system (CNS) (23,8.8%), stomach (22,8.4%), and colon-rectum (22, 8.4%). Interestingly, a large fraction of these cancers (90 out of 261, 34.5%) occurred before the age of 56 years (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In 1990, Lynch et al [22] described the main features of 18 families with a strong aggregation of pancreatic cancer among relatives, estimating that some 6% of pancreatic cancer patients had a family history of the disease and that this phenomenon could be attributed to an as yet undefined genetic predisposition. More recently, Gargiulo et al [23] found that 19 of the 135 pancreatic cancer patients in their study sample could be classified as having suspected Lynch syndrome, and four of these 19 patients had constitutional alterations in the MLH1 or MSH2 genes. Tersmette et al [24] found a high risk of pancreatic cancer among individuals who have at least 3 first-degree relatives with pancreatic neoplasms.…”
Section: Familial Aggregationmentioning
confidence: 95%